Septic arthritis caused by treatment resistant Pseudomonas cepacia. - Matteson, E L (1990)
A case of septic arthritis of the knee caused by Pseudomonas cepacia following an intraarticular corticosteroid injection in a patient with a history of osteoarthritis is presented. This is the second report of this agent causing infection in a diarthrodial joint, which proved difficult to eradicate despite in vitro antibiotic sensitivity.